2020
DOI: 10.1186/s13287-020-01714-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression dynamics of integrin α2, α3, and αV upon osteogenic differentiation of human mesenchymal stem cells

Abstract: Background: The differentiation of human mesenchymal stem cells (hMSCs) into osteoblasts (OBs) is a prerequisite for bone formation. However, little is known about the definitive surface markers for OBs during osteogenesis. Methods: To study the surface markers on OBs, we generated and used monoclonal antibodies (MAbs) against surface molecules on transforming growth factor-β1 (TGF-β1)-treated cancer cells. The generated MAbs were further selected toward expression changes on hMSCs cultured with TGF-β1/bone mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 59 publications
3
9
0
Order By: Relevance
“…The decreased expression of these molecules may be compensatory negative feedback to osteogenic stimulation. A similar effect has been previously demonstrated [ 45 ]. The important role of CD90 and CD73 in osteo-differentiation was demonstrated in vivo since relevant knockout mice exhibit signs of osteopenia phenotype [ 46 , 47 ].…”
Section: Discussionsupporting
confidence: 88%
“…The decreased expression of these molecules may be compensatory negative feedback to osteogenic stimulation. A similar effect has been previously demonstrated [ 45 ]. The important role of CD90 and CD73 in osteo-differentiation was demonstrated in vivo since relevant knockout mice exhibit signs of osteopenia phenotype [ 46 , 47 ].…”
Section: Discussionsupporting
confidence: 88%
“…The protein group on which cell adhesion depends includes mainly ECM proteins, transmembrane proteins, and cytoskeleton proteins [ 39 ]. Among these proteins, integrins, which are an important class of transmembrane proteins, can not only influence cell adhesion, but also regulate the differentiation ability of stem cells by activating downstream signaling pathways [ 40–42 ]. This study found that ITGA10 expression was significantly lower in BMSCs from diabetic patients with implant failure than that in BMSCs from diabetic patients with implant success and normal patients without diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblast adhesion on certain ECM proteins was achieved through binding to αvβ1 integrin [ 39 ]. Various studies have demonstrated that dynamic expression of different integrins is required for the osteogenic differentiation of MSCs [ 40 , 41 ]. The use of graphene material suggests the pivotal role of integrin β1 in ECM roughness recognition, which is involved in osteoblast maturation and MSC differentiation on graphitic carbon-coated surfaces [ 42 ].…”
Section: Discussionmentioning
confidence: 99%